2017
DOI: 10.5507/euj.2017.001
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental motor skills in the first year of school: Associations with prematurity and disability

Abstract: Given the importance of fundamental motor skill proficiency for children's participation in games, sports, and physical activity; our aim was to concurrently examine the fundamental motor skill proficiency of children living with a disability, children born prematurely, and children born full-term without a disability in their first year of school (kindergarten). Participants were 260 children (mean age = 5y9m; boys = 52%); 33 were born prematurely and 12 children lived with a disability. Motor skills were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Continuing with prematurity, no significant differences were found between preterm and full-term preschoolers in both locomotor and object control. The findings are congruent with the research carried out by Temple et al [ 17 ], due to the fact that they observed that prematurity does not exert an effect on object control or locomotor development since both premature infants and non-premature infants scored similarly at the beginning of ECE stage. In the same way, Raniero, Tudella, and Mattos [ 47 ] concluded that healthy premature infants did not present profound delays in motor competence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Continuing with prematurity, no significant differences were found between preterm and full-term preschoolers in both locomotor and object control. The findings are congruent with the research carried out by Temple et al [ 17 ], due to the fact that they observed that prematurity does not exert an effect on object control or locomotor development since both premature infants and non-premature infants scored similarly at the beginning of ECE stage. In the same way, Raniero, Tudella, and Mattos [ 47 ] concluded that healthy premature infants did not present profound delays in motor competence.…”
Section: Discussionsupporting
confidence: 91%
“…According to the World Health Organization [ 16 ], a child is considered premature when a baby is born before 37 weeks of pregnancy. Temple et al [ 17 ] evaluated the motor development of premature and non-premature children, not finding significant differences regarding their effect on the control of objects and/or locomotor development. In addition, these authors added that motor skills at the beginning of the Early Childhood Education (ECE) stage present similar levels with respect to those students who were born prematurely.…”
Section: Introductionmentioning
confidence: 99%
“…Secara teoritis aktivitas fisik berkorelasi dengan kebugaran seseorang (Britton et al, 2020;Taylor et al, 2013), manusia yang memiliki physical fitnes yang tinggi akan semakin bisa mereduksi penyakit-penyakit chronic (Kvaavik et al, 2019). World Health Organisation, American Academy of Pediatrics (AAP) dan Department of Health and Human Services merekomendasikan aktivitas fisik setidaknya 60 menit perhari dengan intensitas moderate (Cavill et al, 2006;Temple et al, 2017;World Health Organization, 2020) (Maric et al, 2020) yang berdasarkan sosiodemographic predictor ditemukan penurunan aktivitas fisik pada remaja, terutama laki-laki yang diduga disebabkan oleh berhentinya mereka dari klub-klub olahraga. Jika melihat hasil tes kebugaran pada penelitian ini, rendahnya kebugaran remaja-remaja tersebut disinyalir tidak lepas dari lamanya kondisi pandemi yang menghantam dunia.…”
Section: Physicalunclassified
“…Therefore, the American Academy of Pediatrics recommends the accumulation of children's screen time activities at least every day no more than 60 minutes and it is used for children over two years of age and it contains good content, it means that it is pedagogically developed specifically for children (Hill et al, 2016). Furthermore, the world health agency, WHO also recommends that children can follow the rules regarding limits on the use of screen-based media by participating in play, games, sports, recreation, and physical education activities (Temple et al, 2017).…”
Section: Introductionmentioning
confidence: 99%